(untitled) - Gossblink, John (New York, 2010)
Designed like a case file, chock-full of notes, journal entries, letters, e-mails, illustrations, and more, Free Thaddeus! is an uproarious middle-grade novel that argues why the irreverent Thaddeus should be released from his in-school suspension and explains the unbelievable circumstances that led to his punishment. Soon readers will be chanting, “Free Thaddeus!
Keywords: Conduct of life,Humorous stories,Truyện cười,Ứng xử của cuộc sống; Fiction,Tiểu thuyết